2005
DOI: 10.1021/op049810b
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient, Mild, Bromide-Free and Acetic Acid-Free Dioxygen Oxidation of p-Nitrotoluene to p-Nitrobenzoic Acid with Metal Phthalocyanine Catalysts

Abstract: Four metal tetracarboxyl phthalocyanines were synthesized and characterized by elemental analysis and mass spectrometry. p-Nitrobenzoic acid was efficiently prepared in high yield from bromide-free and acetic acid-free aerobic oxidation of pnitrotoluene using metal phthalocyanines as catalysts under mild conditions in alkali-methanol solution. Up to 88.8% isolated yield of p-nitrobenzoic acid was obtained with the catalysis of tetracarboxyl phthalocyanine cobalt (0.13 mol %, based on the moles of p-nitrotoluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…When the substrate was replaced with ONT, DNT, MNT and toluene (entry 12-15, Table 1), 92.8% yield of o-nitrobenzoic acid, 93.2% yield of 2, 4-dinitrobenzoic acid, trace of m-nitrobenzoic acid and benzoic acid were obtained respectively, indicating that toluene or MNT as a substrate is much less active than PNT,ONT and DNT in this water-ionic liquid biphasic reaction system. This may be because PNT, ONT and DNT are vulnerable to be ionized by the action of alkali aqueous solution, while toluene and MNT are hard to perform the transformation in this way [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the substrate was replaced with ONT, DNT, MNT and toluene (entry 12-15, Table 1), 92.8% yield of o-nitrobenzoic acid, 93.2% yield of 2, 4-dinitrobenzoic acid, trace of m-nitrobenzoic acid and benzoic acid were obtained respectively, indicating that toluene or MNT as a substrate is much less active than PNT,ONT and DNT in this water-ionic liquid biphasic reaction system. This may be because PNT, ONT and DNT are vulnerable to be ionized by the action of alkali aqueous solution, while toluene and MNT are hard to perform the transformation in this way [7].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, an expensive carbon radical-producing catalyst and acetic acid were used, and a relatively high temperature such as 130°C was adopted [6]. More recently, she and coauthors introduced the bromide-free and acetic acid-free aerobic oxidation of p-nitrotoluene to p-ntrobenzoic acid in high yield using metal phthalocyanines as catalysts under mild conditions in alkali-methanol solution [7,8]. Yet, there will be a potential hazard of explosion when using volatile organic solvent in a pure oxygen environment.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical and optical properties of Pcs are highly sensitive to the environment, especially in the case when they form with functional groups. These groups lead Pcs to a mass of applications such as semiconductors (Ogunsipe et al, 2008), sensors (Schmechel, 2003), fuel cells (Zhang & Hu, 2009), catalysts (Vivo, Ojala, Chukharev, Efimov, & Lemmetyinen, 2009), optical data-storage devices (Song, She, Ji, & Zhang, 2005), etc. Recently, Rollet et al (2008) poly(allylamine hydrochloride) on indium doped tin oxide (ITO) glass as electrochromic and sensing devices.…”
Section: Introductionmentioning
confidence: 99%
“…These achievements indicated that the Pcs are applicable in fabricating multi-layered films and expanding the applications of LBL structured ultra-thin films. Although the LBL deposition of Pcs and polyelectrolytes were successful on various templates such as the ITO substrate (Ingrosso, Petrella, & Cosma et al, 2006;Song et al, 2005), silanized glass (Cooper et al, 1995), and particles (Tao, Li, Hartmanna, & Mohwalda, 2004), the approach on porous three-dimensional (3D) fibrous mats has never been reported. Additionally, it is still a great challenge to combine the water-insoluble Pcs with the water-soluble polyelectrolyte into the multilayer films through the LBL self-assembly technology.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous work, metalloporphyrins and metallophthalocycnines can catalyse oxidation of o/p nitrotoluene and cyclohexane to acid under mild conditions [9][10][11][12]. Quite recently, we reported on a novel method for the synthesis of o-nitrobenzaldehyde by oxygen oxidation of o-nitrotoluene with metalloporphyrins as catalysts in methanol solution [13].…”
mentioning
confidence: 99%